The Concentration of Non-structural Carbohydrates, N, and P in Quercus variabilis Does Not Decline Toward Its Northernmost Distribution Range Along a 1500 km Transect in China - Liu, Jian-Feng; Deng, Yun-Peng; Wang, Xiao-Fei; Ni, Yan-Yan; Wang, Qi; Xiao, Wen-Fa; Lei, Jing-Pin; Jiang, Ze-Ping; Li, Mai-He (Frontiers in Plant Science, 2018)
Understanding the mechanism for plant distribution range is crucial for predicting climate-driven range shift. Compared to altitudinal gradients, less attention has been paid to the mechanisms that determine tree latitudinal range limit. To test whether intrinsic resource limitation contribute to latitudinal range limits of woody species, we investigated the latitudinal variations in non-structural carbohydrates (NSC; i.e. total soluble sugar plus starch) and nutrients (nitrogen and phosphorus) in mature and juvenile Chinese cork oak (Quercus variabilis Blume) along a 1500 km north-south transect in China. During the growing season and dormant season, leaves, branches and fine roots were collected from both mature and juvenile oak in seven sites along the transect. Tissue concentration of NSCs, N and P did not decrease with increasing latitude irrespective of various sampling seasons and ontogenetic stages. Furthermore, higher level of NSCs and N in tissues of juveniles relative to mature trees was found during the dormant season. Partial correlation analysis also revealed that during the dormant season, soluble sugar, NSC, ratio of soluble sugar to starch and nitrogen of tissues studied were correlated positively with latitude, but negatively with precipitation and mean temperature of dormant season. Our results suggest that carbon or nutrient availability may not be a determinant factor for latitudinal range limit of the studied species. Further studies should be carried out at community or ecosystem level with multi-species to test the roles of other factors such as regeneration, competition and disturbance, rather than resource availability, in determining a species’ northern distribution limit.